Measurement of extracellular fluid compartment volume using inulin: - Al-Ani, Ghassan T. (Journal of the Faculty of Medicine Baghdad, 2008)
Background:There is a need to find methods to assess the size of the extracellular fluid (ECF) volume without involving radioactive tracers. For this purpose, the simple delusion method was usedto measure the ECF in rabbits and the inulin which is a polysaccharide was used as a marker of ECF measurement.Methods:18 male rabbits were used in this study. 8 of these animals were bilaterally nephroctomized to calculate the exact time to get diffusion equilibrium time after a bolus dose of inulin at adose of 25mg/kg of a solution of inulin 10 mg/ml. intravenously. The blood samples were taken after 1, 15, 45, 60, 90, 120, and 180 min.Results:ECF volume was about 144.5 to 149.7 ml/kg depending on the inulin concentration changing with time because the equilibrium time of inulin and the ECF could not beobtained to the end of the experiment. Conclusion:The inulin takes a space in the body fluids differ than the true ECF volume. It is better to use the term "inulin space" to reflect such measurements rather than the ECF volume.